Iraqi EFL Learners' Awareness of Semantic Use of Two- Part Verbs (Journal of the College of Basic Education, 2022)
The necessity of vocabulary teaching nowadays, especially phrasal verbs teaching, has gained more importance than before. Not only scholars but foreign language teachers have realized that both grammar and vocabulary teaching cannot be ignored. Phrasal verbs as an important part of the English language and are central to English grammar structure, there is a strong tendency in informal colloquial English to use phrasal verbs. So, EFL learners should have adequate knowledge of phrasal verbs, and mastering the use of such verbs is a crucial prerequisite to having fluent students. This study aimed at identifying the Iraqi EFL learners' awareness of the semantic use of two-part verbs by answering the following questions: Which verb do students prefer to use, one-part verbs or two-part verbs?Is there a significant difference between students' awareness of one-part verbs and two-part verbs? The sample of the study consisted of 80 female and male students who have randomly been chosen from the third-grade/ Department of English /College of Arts/Al-Mustansiriyah University during the academic year 2011-2012. In order to achieve the aims of a recent study, a test consisting of two parts has been constructed. The test is submitted to a jury of specialties to ensure its face validity then it is administrated to the selected sample of EFL college students. Moreover, the results indicated that there is a statistically significant difference in students' awareness of one-part verbs and two-part verbs and in favor of one-part verbs which means that they encounter difficulties in using two-part verbs semantically and this ensures that the aims of the recent study have been attained. In light of the obtained results, some conclusions are drawn and a number of suggestions and recommendations are made